Evaluation of UV-A and solar light photocatalytic hydrogen gas evolution from olive mill wastewater. (6th April 2015) - Speltini, Andrea; Sturini, Michela; Maraschi, Federica; Dondi, Daniele; Fisogni, Gabriele; Annovazzi, Enrico; Profumo, Antonella; Buttafava, Armando
Abstract This work presents the results obtained in using olive mill wastewater (OMW) as sacrificial agent for the photocatalytic H2 evolution from water, at ambient temperature and pressure. The effects of irradiation time, catalyst amount, pH, and OMW concentration have been investigated. Under the best experimental conditions (4 h UV-A irradiation, 2 g L−1 Pt/TiO2, OMW 3.3% v/v, COD 944 mg L−1, pH 3) up to 44 μmol H2 were generated from aqueous samples. Consecutive irradiation cycles (4 × 4 h) on the same sample provided ca. 280 μmol H2, corresponding to 82% of the yield observed, under the same conditions and COD value, by using glucose as test sacrificial agent. H2 evolution was strongly improved (+81%) by pre-treating OMW with magnesium silicate (125 g L−1, 6 h contact), achieving a production of ca. 80 μmol H2 by 4 h UV-A irradiation. The possibility to exploit sunlight in the photocatalytic process was gained by using Eosin Y/Pt/TiO2. Under solar light the H2 yield resulted to be 66% with respect to that obtained by UV-A radiation. Beside some general mechanistic aspects of the photocatalytic process, benefits and drawbacks in recycling OMW for photocatalytic H2 evolution from water have been highlighted.